Giant Gallstones – a Systematic Review - Alkhezzi, Amjaad; Salati, Sajad Ahmad; Alsulaim, Lamees Sulaiman; Elmuttalut, Mohammad Ahmed; Alsalamah, Yasir Ahmed (Lietuvos chirurgija, 2024)
Giant gallstones are rare occurrences and measure 5 cm in any one dimension. They present unique set of features and complications. Due to their rarity, we conducted this systematic review to investigate the profile of patients with giant gallstones applying seven variables. For this study, we used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. After an initial search of 111 peer reviewed articles from reliable sources, we included 29 articles for this study enrolling 30 patients with mean age of 66.7 years. Majority (97%) were symptomatic, reporting with cholecysto-enteric fistula/gallstone ileus (33%), acute cholecystitis (30%) and chronic dyspepsia (24%). The management options adopted included open cholecystectomy (48%), laparoscopic cholecystectomy (33%), endoscopic lithotripsy (6%) and conservative management (6%).